Carbon Sequestration with Reforestations and Biodiversity-Scenic Values - A. Caparrós; E. Cerdá; P. Ovando; P. Campos (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper presents an optimal control model to analyze reforestations with two different species, including commercial values, carbon sequestration and biodiversity or scenic values. We solve the model qualitatively with general functions and discuss the implications of partial or total internalization of environmental values, showing that internalizing only carbon sequestration may have negative impacts on biodiversity-scenic values. To evaluate the practical relevance, we compare reforestations in the South-west of Spain with cork-oaks (a slow growing native species) and with eucalyptus (a fast growing alien species). We do the analysis with two different carbon crediting methods: the Carbon Flow Method and the Ton Year Accounting Method. With the .first method forest surface increases more, but using mainly eucalyptus. With the second, additional reforestations are done mainly using cork-oaks. We value the impact on visitors of these reforestations using stated preferences methods, showing that when these values are internalized cork-oaks are favored.
Keywords: Q23; Q26; Q51; Q57; 330; Optimal Control; Forests; Carbon; Sequestration; Biodiversity; Scenic; Stated Preferences; Carbon Accounting